STUDI KARAKTERISTIK RUANG PADA BANGUNAN RUMAH TINGGAL KOLONIAL DI KAWASAN BANGIREJO TAMAN YOGYAKARTA - Wihardyanto, Dimas; Ikaputra, Ikaputra (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2020)
Abstrak_ Bangirejo Taman merupakan salah satu kawasan perumahan untuk para pegawai pemerintahan kolonial Belanda (amtenar) yang berada di Yogyakarta. Penggunaan kata taman dibelakang Bangirejo pada kawasan perumahan ini untuk memperjelas perbedaan karakteristik kawasan perumahan ini dengan permukiman di sekitarnya dimana kawasan perumahan Bangirejo Taman didesain dengan adanya taman lingkungan di tengah kawasan. Peneliti menggunakan pendekatan interpretive historical research untuk mendapatkan karakteristik arsitektur tata ruang yang asli mencakup tata massa, tata ruang, orientasi, sirkulasi, serta hubungan dan hirarki ruang. Karakteristik tersebut didapatkan dengan cara melakukan proses gambar rekonstruksi tata ruang pada perumahan kolonial Bangirejo Taman berdasarkan analisis kesamaan dan perbedaan gambar denah 7 buah rumah tinggal yang dipilih dengan pendekatan snowball sampling. Dari hasil analisis diketahui bahwasanya karakteristik tata ruang bangunan rumah tinggal kolonial di Kawasan Bangirejo Taman dirancang terutama untuk memenuhi aspek fungsionalitas. Hal ini tampak dari adanya pemisahan antara bangunan inti (hoofdgebouw), dan bangunan servis (bijgebouw) yang keduanya dihubungkan oleh selasar. Karakteristik tersebut diperkuat dengan pola konfigurasi dan sirkulasi ruang pada bangunan inti dan servis yang tunggal dan sederhana. Selain memenuhi fungsionalitas ruang, perancangan rumah tinggal kolonial di Kawasan Bangirejo Taman juga memperhatikan higienitas ruang dengan meletakkan bangunan inti dan bangunan servis di bagian tengah dari lahan agar mendapatkan sinar matahari yang cukup, dan prinsip cross ventilation dapat diterapkan.Kata kunci : Arsitektur Kolonial; Karakteristik Ruang; Rumah Tinggal Kolonial; Interpretive Historical Research. Abstract_ BangirejoTaman is a residential area for the employees of the Dutch colonial government (Amtenaar) located in Yogyakarta. The use of the word taman (park) behind Bangirejo in this residential area is to clarify the differences in the characteristics of this residential area with the surrounding settlements where the BangirejoTaman residential area is designed with a neighborhood park in the middle of the area. Researchers used an interpretive historical research approach to obtain the characteristics of the original spatial architecture including spatial planning, spatial planning, orientation, circulation, and relationships, and hierarchical space. These characteristics were obtained by carrying out a process of drawing spatial reconstruction in the colonial housing estate BangirejoTaman based on an analysis of the similarities and differences in the drawings of 7 residential planes that were selected using a snowball sampling approach. From the results of the analysis, it is known that the characteristics of the spatial structure of colonial residential buildings in the BangirejoTaman Area are designed primarily to meet the functional aspects. This can be seen from the separation between the core building (hoofdgebouw), and the service building (bijgebouw) which are both connected by a hallway. These characteristics are reinforced by the pattern of configuration and circulation of space in the core building and a single and simple service. In addition to fulfilling spatial functionality, the design of colonial dwellings in the BangirejoTaman Area also pays attention to space hygiene by placing core buildings and service buildings in the middle of the land in order to get enough sunlight, and the principle of cross ventilation can be applied.Keywords: Colonial Architecture; Spatial Characteristics; Colonial House; Interpretive Historical Research.